2016
DOI: 10.1097/prs.0000000000002534
|View full text |Cite
|
Sign up to set email alerts
|

Postmastectomy Radiation Therapy and Two-Stage Implant-Based Breast Reconstruction: Is There a Better Time to Irradiate?

Abstract: Background The ideal timing of post-mastectomy radiation therapy (PMRT) in the setting of two-staged implant-based breast reconstruction remains unclear. In this cohort study, we sought to determine whether complication rates differed between patients who received PMRT following tissue expander placement (TE-XRT) and those who received PMRT after exchange for permanent implant (Implant-XRT) utilizing prospective, multicenter data. Methods Eligible patients in the Mastectomy Reconstruction Outcomes Consortium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
40
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(51 citation statements)
references
References 26 publications
6
40
0
5
Order By: Relevance
“…The Mastectomy Reconstruction Outcomes Consortium (MROC) study represents the largest and most thorough review of postmastectomy radiation therapy and two-stage implant-based reconstruction. 36 In this study, 150 patients were identified from 11 institutions across North America (â–șTable 1). There were 104 patients who received radiation to their tissue expander (69.3%) compared with 46 who received radiation to their implant (30.7%).…”
Section: Radiation In the Setting Of Two-stage Expander-implant Reconmentioning
confidence: 99%
“…The Mastectomy Reconstruction Outcomes Consortium (MROC) study represents the largest and most thorough review of postmastectomy radiation therapy and two-stage implant-based reconstruction. 36 In this study, 150 patients were identified from 11 institutions across North America (â–șTable 1). There were 104 patients who received radiation to their tissue expander (69.3%) compared with 46 who received radiation to their implant (30.7%).…”
Section: Radiation In the Setting Of Two-stage Expander-implant Reconmentioning
confidence: 99%
“…There was overwhelming panel preference for a delayed‐immediate implant‐based approach when PMRT was likely, although a consensus could not be reached on whether it was preferable to irradiate an expander‐implant versus a permanent implant. Recent data from the MROC longitudinal cohort study showed no differences in either clinical or cosmetic outcomes for irradiation of an expander compared with a permanent implant.…”
Section: Resultsmentioning
confidence: 99%
“…The generic reference to ‘breast reconstruction’ was intended to capture all articles addressing the type and timing of breast reconstruction. Two authors independently reviewed abstracts of all studies published between 1985 and 2014, and the full texts of those studies published in 2015–2017. Levels of clinical evidence (LoE) were evaluated for each publication and scored from I to V by employing Oxford criteria.…”
Section: Methodsmentioning
confidence: 99%
“…We also identified a significantly higher rate of reconstruction failure at 5 years with TE/I, compared to AR, for patients with overweight BMI (25.1‐30) and obese BMI (>30), but not for patients with normal BMI (≀25). It is well established in the literature that patients with current or previous smoking history and BMI ≄ 30 have a significant higher risk of failure of reconstruction . Additionally, these factors also increase the risk of infection and data have demonstrated that the most common etiology of implant‐based reconstruction failure is infection .…”
Section: Discussionmentioning
confidence: 99%
“…It is well established in the literature that patients with current or previous smoking history and BMI ≄ 30 have a significant higher risk of failure of reconstruction. [16][17][18][19] Additionally, these factors also increase the risk of infection and data have demonstrated that the most common etiology of implant-based reconstruction failure is infection. 20 We have identified that infections account for a substantial proportion of reconstruction failures in our series.…”
Section: Discussionmentioning
confidence: 99%